Growth and auto-oxidation of Pd on single-layer AgOx/Ag(111). Issue 11 (4th March 2020) - Mehar, Vikram; O'Connor, Christopher R.; Egle, Tobias; Karatok, Mustafa; Madix, Robert J.; Friend, Cynthia M.; Weaver, Jason F.
Abstract : Pd is auto-oxidized during deposition onto AgO x and undergoes a transition from single to bi-layer growth at low Pd coverage. Abstract : We investigated the growth and auto-oxidation of Pd deposited onto a AgO x single-layer on Ag(111) using scanning tunneling microscopy (STM) and X-ray photoelectron spectroscopy (XPS). Palladium initially grows as well-dispersed, single-layer clusters that adopt the same triangular shape and orientation of Ag n units in the underlying AgO x layer. Bi-layer clusters preferentially form upon increasing the Pd coverage to ∼0.30 ML (monolayer) and continue to develop until aggregating and forming a nearly conformal Pd bi-layer at a coverage near 2 ML. Analysis of the STM images provides quantitative evidence of a transition from single to bi-layer Pd growth on the AgO x layer, and a continuation of bi-layer growth with increasing Pd coverage from ∼0.3 to 2 ML. XPS further demonstrates that the AgO x layer efficiently transfers oxygen to Pd at 300 K, and that the fraction of Pd that oxidizes is approximately equal to the local oxygen coverage in the AgO x layer for Pd coverages up to at least ∼0.7 ML. Our results show that oxygen in the initial AgO x layer mediates the growth and structural properties of Pd on the AgO x /Ag(111) surface, enabling the preparation of model PdAg surfaces with uniformly distributed single or bi-layer Pd clusters. Facile auto-oxidation of Pd by AgO x further suggests that oxygen transfer from Ag to Pd could play a role in promoting oxidation chemistry of adsorbed molecules on PdAg surfaces.